Highly virulent avian brood-parasitic species show elevated embryonic metabolic rates at specific incubation stages compared to less virulent and non-parasitic species - McClelland, Stephanie C; Lund, Jess; Dixit, Tanmay; Hamama, Silky; McClean, Luke A; Spottiswoode, Claire N; White, Craig R; Louder, Matthew I M; Hauber, Mark E; Honza, Marcel; Portugal, Steven J (Biology letters, 2024)
As the avian embryo grows and develops within the egg, its metabolic rate gradually increases. Obligate avian brood-parasitic birds lay their eggs in the nests of other species to avoid the costs of parental care, and all but one of these brood-parasitic species are altricial at hatching. Yet the chicks of some altricial brood-parasitic species perform the physically demanding task of evicting, stabbing or otherwise killing host progeny within days of hatching. This implies a need for high metabolic rates in the embryo, just as precocial species require. Using flow-through respirometry in situ, we investigated embryonic metabolic rates in diverse avian brood parasite lineages which either kill host offspring (high virulence) or share the nest with host young (low virulence). High-virulence brood parasite embryos exhibited higher overall metabolic rates than both non-parasitic (parental) species and low-virulence parasites. This was driven by significantly elevated metabolic rates around the halfway point of incubation. Additionally, a fine-scale analysis of the embryos of a host-parasitic pair showed faster increases in metabolic rates in the parasite. Together these results suggest that the metabolic patterns of the embryos of high-virulence parasites facilitate their early-life demands.
Keywords: embryo nesavčí; cowbirds; Embryo, Nonmammalian; virulence; Energy Metabolism; embryo metabolism; Birds; Nesting Behavior; energetický metabolismus; cuckoos; zvířata; Virulence; Host-Parasite Interactions; honeyguides; interakce hostitele a parazita; brood parasitism; respirometry; ptáci; hnízdění; Animals